Transiting exoplanets from the CoRoT space mission - III. The spectroscopic transit of CoRoT-Exo-2b with SOPHIE and HARPS - Bouchy, F; Queloz, D; Deleuil, M; Loeillet, B; Hatzes, A; Aigrain, S; Alonso, R; Auvergne, M; Baglin, A; Barge, P; Benz, W; Borde, P; et al. (2008)
We report on the spectroscopic transit of the massive hot-Jupiter CoRoT-Exo-2b observed with the high-precision spectrographs SOPHIE and HARPS. By modeling the radial velocity anomaly occurring during the transit due to the Rossiter-McLaughlin (RM) effect, we determine the sky-projected angle between the stellar spin and the planetary orbital axis to be close to zero = 7.2 4.5 deg, and we secure the planetary nature of CoRoT-Exo-2b. We discuss the influence of the stellar activity on the RM modeling. Spectral analysis of the parent star from HARPS spectra are presented. © 2008 ESO.